2022
DOI: 10.1111/rda.14228
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different concentrations of melatonin on ram epididymal spermatozoa recovered post‐mortem under oxidative stress conditions and storage at 4°C

Abstract: Sheep breeding has greatly benefited from artificial insemination transferring superior genetic material from a few males to many females (Maxwell & Watson, 1996). Cold storage is one way to maintain sperm viability for a long period and reduce sperm metabolism.However, long-term storage degrades the quality of semen (Perumal et al., 2013). One of these decline causes is the production of reactive oxygen species (ROS) by semen cells (Perumal et al., 2011(Perumal et al., , 2013. ROS are generally necessary for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 54 publications
0
0
0
Order By: Relevance
“…In the following decade (2000–2010), the presence of melatonin in seminal plasma and its antioxidant effects were found to be highly correlated with the activity of the three antioxidant enzymes superoxide dismutase, glutathione reductase and catalase ( Casao et al, 2010a ). More recent studies (from 2011 to date) have demonstrated direct effects of melatonin on ram spermatozoa, reducing apoptotic effects and modulating sperm capacitation to improve fertilisation rates ( Shayestehyekta et al, 2022 ; Kumar et al, 2022 ). This was the guideline for the development of studies on the addition of different concentrations of melatonin to diluted semen to improve its quality in the freeze-thaw process since free radicals (ROS) are formed at this stage ( Rizkallah et al, 2022 ), which have an oxidative effect when they accumulate excessively, altering the sperm cell membrane, resulting in a reduction in sperm motility and viability.…”
Section: Administration Of Hormonal Products To Stimulate Sexual Acti...mentioning
confidence: 99%
“…In the following decade (2000–2010), the presence of melatonin in seminal plasma and its antioxidant effects were found to be highly correlated with the activity of the three antioxidant enzymes superoxide dismutase, glutathione reductase and catalase ( Casao et al, 2010a ). More recent studies (from 2011 to date) have demonstrated direct effects of melatonin on ram spermatozoa, reducing apoptotic effects and modulating sperm capacitation to improve fertilisation rates ( Shayestehyekta et al, 2022 ; Kumar et al, 2022 ). This was the guideline for the development of studies on the addition of different concentrations of melatonin to diluted semen to improve its quality in the freeze-thaw process since free radicals (ROS) are formed at this stage ( Rizkallah et al, 2022 ), which have an oxidative effect when they accumulate excessively, altering the sperm cell membrane, resulting in a reduction in sperm motility and viability.…”
Section: Administration Of Hormonal Products To Stimulate Sexual Acti...mentioning
confidence: 99%
“…Saberivand et al [117] assayed SOD activity in Romanov ram spermatozoa (Tabriz, Iran), based on the inhibition of nitro blue tetrazolium (NBT) reduction by superoxide radicals to blue-colored formazan. The reaction was followed by reading at 560 nm.…”
Section: Sod In Spermatozoamentioning
confidence: 99%